(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study investigates the efficacy of incorporating authentic materials into primary school curriculum to bolster students’ listening skills. With the increasing importance of communicative competence in language acquisition, particularly in the early stages of education, the utilization of authentic materials presents a promising avenue for pedagogical innovation. Authentic materials, sourced from real-life contexts, offer rich linguistic features and cultural nuances, potentially fostering more engaging and effective learning experiences. This annotated research delves into various methodologies and strategies employed in integrating authentic materials into listening skill development activities within primary school settings. Through a comprehensive review of existing literature, the study assesses the impact of authentic materials on students’ listening comprehension, language proficiency, and motivation. Moreover, it examines practical considerations, such as material selection, task design, and classroom implementation techniques. The findings contribute valuable insights into the theoretical framework and practical implications of utilizing authentic materials for enhancing listening skills among primary school students, offering educators evidence-based strategies to optimize language learning outcomes.